A Telemonitoring Tool based on Serious Games Addressing Money Management Skills for People with Intellectual Disability - Lopez-Basterretxea, Asier (MDPI, 2014)
This article presents a telemonitoring tool based on computer games, aimed at money management skill improvement for people with Intellectual Disabilities (ID). The presented tool is divided into two parts: on one hand, some training activities related to payments and currency discrimination based on Serious Games are proposed to the user using a multitouch device. On the other hand, the psychologists and specialist who work with them, can access to the Serious Games results using an online application in order to evaluate their evolution. The results are measured according to the number of errors they have during the proposed activities, the time they need to complete them and the score. The article show the results of an experiment made with a clinical sample of 12 users with ID between 12 and 15 years, taking into account that all of them are capable of correct oral communication and they do not have severe physical coordination problems. Only two users completed all the games without errors. Males obtained a mean of 28.25 errors, whereas females obtained a mean of 17.75. The results show significant difference between the selection of games 1, 2 or 3, because all of them prefer the game 1 related with “Payments” probably because it permits more interaction using the multitouch device. The authors also made a qualitative evaluation and the results have been very promising and satisfactory.